The Relation between the Characteristics of Parents and the Incidence of Stunting in Elementary School Children in the Working Area of the Air Beliti Health Center - Dita Anggriani Lubis; Mohammad Zulkarnain; Rostika Flora; Risnawati Tanjung (Budapest International Research and Critics University, 2021)
Stunting is a failure of growth and development experienced by children due to inadequate nutritional intake for a long time, recurrent infectious diseases, and inadequate psychosocial stimulation. The incidence of stunting is higher in rural areas than in urban areas. This study aims to analyze the relationship between maternal characteristics and the incidence of stunting in elementary school children in the Air Beliti Health Center working area. The study was conducted on elementary school children in the working area of the Air Beliti Health Center, Musi Rawas Regency. The design of this study used a cross-sectional design, with a total sample of 84 respondents who were taken randomly and met the inclusion criteria. Determination of stunting is based on anthropometric measurements, while the characteristics of parents are assessed using a questionnaire. Furthermore, the data were analyzed using Univariate, Bivariate, and Multivariate statistical tests. The results of anthropometric measurements showed that children who experienced stunting were 41 people, 48.8%. Based on the characteristics of the parents, it was found that 54.8% of fathers and 50% of mothers had low education, 65.5% of fathers and 75% of mothers worked as farmers, 58.3% of parents had low economic status, and 51.2% parents marry at a young age. There is a significant relationship between married age (p = 0.049), maternal education (0.029), and stunting incidence. Based on the multivariate test results, it was found that the most dominant factor related to the incidence of stunting was the age at marriage (p = 0.000; OR = 80.079). Parents who marry in their teens have a risk of 80,079 times having stunting children. Conclusion: adolescent marriage is associated with the incidence of stunting in elementary school children in the work area of the Air Beliti Health Center.